1986
DOI: 10.1007/bf02264077
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal steroidogenesis and the possible role of steroid glucuronides as sex pheromones in two species of teleosts

Abstract: In general, female zebrafish,Brachydanio rerio, ovulate only in the presence of males. The stimulant must be pheromonal as even male holding water is capable of inducing ovulation. After ovulation the mating phase begins. During this phase the male follows the female and oviposition as well as fertilization takes place. Both the ovulation and the mating are controlled by pheromones synthesized by the gonads. Ovulation can be induced by testicular homogenates. After the lipid material has been extracted from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

1987
1987
1994
1994

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 12 publications
0
31
0
1
Order By: Relevance
“…In zebrafish, Brachydanio verio, intersexual attraction can be caused by extracts of postovulatory zebrafish ovaries (van den Hurk and Lambert 1983;Lambert et al, 1986) and ovulation can be induced by male holding water (Chen and Martinich, 1975). Little is known about the biochemical nature of these fish pheromones.…”
Section: Pheromonesmentioning
confidence: 99%
“…In zebrafish, Brachydanio verio, intersexual attraction can be caused by extracts of postovulatory zebrafish ovaries (van den Hurk and Lambert 1983;Lambert et al, 1986) and ovulation can be induced by male holding water (Chen and Martinich, 1975). Little is known about the biochemical nature of these fish pheromones.…”
Section: Pheromonesmentioning
confidence: 99%
“…In the African catfish steroid glucuronides can act as pheromones (Lambert et al, 1986;Resink et al, 1987). The present results indicate that the skin, and in particular its epithelial cells, is capable of synthesizing steroid glucuronides.…”
Section: Discussionmentioning
confidence: 51%
“…However, the possibility of steroid glucuronides, formed in the skin, playing a significant role as sex pheromones cannot be ruled out. In the African catfish, steroid glucuronide fractions, obtained from seminal vesicles and ovaries, possess pheromonal functions (Lambert et al, 1986;Resink et al, 1987). Pheromonal properties of steroid glucuronides were also demonstrated in zebrafish, B. rerio (Van den Hurk and Lambert, 1983) and in G. *jozo (Colombo et al, 1980).…”
Section: Discussionmentioning
confidence: 95%
“…Recent experiments by Resink et al (198713) -see also Lambert et al (1986) and Van Oordt (1986) -have shown that the fluid produced by the seminal vesicles of African catfish is involved in the attraction of females after ovulation. Preliminary experiments have made it possible to identify three steroid glucuronides in this fluid, namely 5j?-pregnane-3cu,l7a-diol-20-one-glucuronide, 5P-androstane-3a,l7/?-diol-glucuronide and etiocholanolone-glucuronide ( Schoonen, in preparation).…”
Section: Testosterone-glmentioning
confidence: 99%
“…Steroid glucuronides of testicular origin have been described for the teleosts Gobius paganellus (Colombo et al, 1970)) G. jozo (Colombo et al, 1977), the rainbow trout (Hews and Kime, 1978)) the goldfish (Kime, 1980)) Sarotherodon mossambicus (Kime and Hyder, 1983) and the zebrafish, Brachydanio rerio (Lambert et al, 1986;Van Oordt, 1986;Van Den Hurk et al, 1987b). In G. jozo etiocholanolone-glucuronide attracts ovulated females (Colombo et al, 1980(Colombo et al, , 1982.…”
Section: Introductionmentioning
confidence: 99%